The Influence of Democratic Leadership Style, Work Productivity and Career Development on Work Motivation on Employees: Pengaruh Gaya Kepemimpinan Demokratis, Produktivitas Kerja dan Pengembangan Karir Terhadap Motivasi Kerja pada Karyawan - Bairawati, Cindy; Prapanca, Detak (Indonesian Journal of Law and Economics Review, 2023)
The purpose of this study was to determine the effect of democratic leadership style, work productivity and career development partially and simultaneously and to determine the most influential variables on work motivation in CV employees. Himpunan Abadi Surabaya. The research method used a quantitative approach with questionnaire data collection techniques distributed to 100 respondents. Respondents were taken based on one of the Non Probability Sampling by using the Saturation Sampling technique (Sample Saturated) this technique is used when the entire population is used as a sample. Because the existing population in the company CV. As many as 100 of the Surabaya Abadi Association, the population will be used fully as a sample, namely 100 respondents who were tested for validity, reliability, classical assumptions, multiple linear regression, partial tests, simultaneous tests, multiple correlation coefficient tests and multiple determination tests. The results showed that the partial test showed Democratic Leadership Style, Work Productivity and Career Development partially on work motivation at CV. Himpinan Abadi Surabaya, Simultaneous test shows that Democratic Leadership Style, Work Productivity and Career Development have a simultaneous influence on work motivation and Democratic Leadership Style is the variable that has the most significant influence on work motivation.